2021
DOI: 10.3390/plants10050828
|View full text |Cite
|
Sign up to set email alerts
|

Extracts of Poplar Buds (Populus balsamifera L., Populus nigra L.) and Lithuanian Propolis: Comparison of Their Composition and Biological Activities

Abstract: Balsam poplar and black poplar (Populus balsamifera L. and Populus nigra L.) buds that grow in Lithuania are the primary source of propolis, therefore it is proper to evaluate and compare the composition of these raw plant materials and propolis quantitatively and qualitatively. Propolis and balsamic poplar bud extract are dominated by p-coumaric acid and black poplar-caffeic acid. Antioxidant activity was evaluated by DPPH (2,2-diphenyl-1-picrylhydrazyl), ABTS (2,2-azino-bis(3-ethylbenzothiazoline-6-sulfonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 66 publications
(88 reference statements)
5
23
0
2
Order By: Relevance
“…According to the direct comparison with commercial standards and the time of retention (Tr), the pinocembrin was verified as the most abundant compound present. In the three samples we identified the presence of other polyphenols such as galangin, quercetin, apigenin and caffeic acid phenethyl ester (CAPE); these results were similar to previous studies [ 13 , 14 , 15 ].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…According to the direct comparison with commercial standards and the time of retention (Tr), the pinocembrin was verified as the most abundant compound present. In the three samples we identified the presence of other polyphenols such as galangin, quercetin, apigenin and caffeic acid phenethyl ester (CAPE); these results were similar to previous studies [ 13 , 14 , 15 ].…”
Section: Resultssupporting
confidence: 91%
“…Chromatographic and spectrometric studies aimed at quantifying total compounds showed differences in the results in previous studies, where calibration curves were performed with caffeic acid and not gallic acid or catechin and not using a mixture of pinocembrin–galangin (2:1 proportion) using the Folin–Ciocalteu method. These flavanones and dihydroflavonols are the main components in poplar-type propolis, as described by several authors [ 3 , 15 ]…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…No statistically significant difference (p > 0.05) was determined between the amounts of active ingredients in the tested gels. The test results confirmed that the main components in poplar buds are phenolic acids and flavonoids [25]. The results of quantitative analysis showed that in situ gels with poplar buds extract could be used in ophthalmology as sources of polyphenolic compounds [81].…”
Section: Bioactive Componds and Antioxidant Activity Of In Situ Gelsmentioning
confidence: 57%
“…Balsam poplar buds, as with propolis, are a source of phenolic acids and flavonoids. Researchers have found that p -coumaric acid predominates in both ethanolic propolis and balsam poplar buds extracts collected in Lithuania [ 25 ]. Poplar buds, due to their antibacterial [ 26 ], antioxidant [ 27 ], and anti-inflammatory [ 28 ] action, are a potential active material in the production of eye drops.…”
Section: Introductionmentioning
confidence: 99%